2018
DOI: 10.1039/c8cp02323a
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between magnetic anisotropies in CoAu and Co films and antidot arrays: effects on the spin configuration and hysteretic behavior

Abstract: We studied (i) a set of three Co : Au continuous films, grown by sputtering co-deposition (∼80 nm thick) with concentration ratios of 2 : 1, 1 : 1 and 1 : 0 (i.e., a pure Co film was also included), and (ii) a corresponding set of antidot arrays, produced by nanosphere lithography with the same hexagonal pattern (nominal lattice periodicity ∼520 nm). The samples were investigated by atomic and magnetic force microscopy and SQUID magnetometry. A twofold aim was fulfilled: to gain information on the magnetism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…It has been found that the Co1-xAux alloy is typically immiscible in bulk phases 10 . Moreover, the magnetic layer thickness for PMA can be enhanced when the Au concentration increases up to a certain extent in the Co1-xAux alloy 11 . In this context, emphasizing on the higher PMA, we study the magnetic behavior of Al2O3(0001)/Pt (400 Å)/Re (10 Å)/Co1-xAux (20 Å)/Pt (30 Å) alloys, where the Au concentration is varied from x = 0 to 25%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the Co1-xAux alloy is typically immiscible in bulk phases 10 . Moreover, the magnetic layer thickness for PMA can be enhanced when the Au concentration increases up to a certain extent in the Co1-xAux alloy 11 . In this context, emphasizing on the higher PMA, we study the magnetic behavior of Al2O3(0001)/Pt (400 Å)/Re (10 Å)/Co1-xAux (20 Å)/Pt (30 Å) alloys, where the Au concentration is varied from x = 0 to 25%.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, emphasizing on the higher PMA, we study the magnetic behavior of Al2O3(0001)/Pt (400 Å)/Re (10 Å)/Co1-xAux (20 Å)/Pt (30 Å) alloys, where the Au concentration is varied from x = 0 to 25%. The few available literature studies confirm either the amorphous nature of the Co1-xAux alloy or the existence of two phases, namely Co and Co1-xAux nano alloys 11,12 . However, we discuss the crystallinity of bimetallic Co1-xAux alloy using reflection high energy electron diffraction (RHEED) patterns and cross-sectional transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%